Single Gaussian Chaotic Neuron: Numerical Study and Implementation in an Embedded System - Torres Treviño, Luis Martín; Rodríguez Liñan, Ángel; González Estrada, Luis Lauro; González Sanmiguel, Gustavo (2013)
Artificial Gaussian neurons are very common structures of artificial neural networks like radial basis function. These artificial neurons use a Gaussian activation function that includes two parameters called the center of mass (cm) and sensibility factor (